2015
DOI: 10.4103/1735-1995.168382
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the relationship between the environmental air pollution, clinical risk factors, and hospital mortality due to myocardial infarction in Isfahan, Iran

Abstract: Background:This study aimed to determine the relationship between the environmental factor, clinical risk factors, and individual variables with mortality due to acute myocardial infarction (MI) in Isfahan.Materials and Methods:This cross-sectional study was performed between April 2012 and March 2013. The data on the patients’ mortality due to MI in Isfahan were obtained from the MI National Registry. The international classification system (ICD10: I21-I22) was used to diagnose MI. The air quality indicators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Particle pollution which is more known as PM is linked with most of pulmonary and cardiac-associated morbidity and mortality. [3334] They have varied in size ranging mostly from 2.5 to 10 μm (PM 2.5 to PM 10 ).…”
Section: Toxicology Of Air Pollutionmentioning
confidence: 99%
“…Particle pollution which is more known as PM is linked with most of pulmonary and cardiac-associated morbidity and mortality. [3334] They have varied in size ranging mostly from 2.5 to 10 μm (PM 2.5 to PM 10 ).…”
Section: Toxicology Of Air Pollutionmentioning
confidence: 99%
“…According to WHO, particulate pollution, ground-level O 3 , CO, sulfur dioxide (SO 2 ), nitrogen oxides (NO x ), and lead (Pb) are the six major air pollutants that adversely affect human health and the environment (Ghorani-Azam et al 2016). Particulate matter (PM) pollutant is responsible for most of the pulmonary and cardiac diseases, and mortality (Sadeghi et al 2015;Sahu et al 2014). According to a study of Global Burden of Disease (GBD), PM 2.5 is the 5th most vulnerable pollutant responsible for the death of humans worldwide, which triggered 4.2 million deaths in the year 2015 (Cohen et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The different sources emit a set of long-term harmful air pollutants to exposed populations [ 14 , 15 ]. Several studies revealed that PM affect the upper part of the respiratory system, causing irritation of the trachea, sore throat, and flowing nostrils, among most exposed people [ 11 , 17 ]. These PM are harmful to health because they can block and inflame nasal and bronchial passages, thus causing a variety of respiratory-related conditions that lead to illness or death.…”
Section: Discussionmentioning
confidence: 99%